Glucose transporter deficiency syndrome type 1: a case report - E. A. Kulish; A. S. Kotov; E. V. Mukhina; Y. Y. Kotalevskaya; D. V. Svetlichnaya; M. V. Panteleeva (Русский журнал детской неврологии, 2019)
The authors present a unique clinical observation of the case of a hereditary deficiency of a type 1 glucose transporter, also called de Vivo disease. The type 1 glucose transporter deficiency syndrome (OMIM: 606777, ORPHA: 71277) is an extremely rare genetic disease associated with mutations in the SCL2A gene encoding the transfer of glucose across the blood-brain barrier. The clinical case, given in the article, replenishes the piggy bank of genetically verified glucose transport disruption syndromes leading to the development of polymorphic neurological disorders. The syndrome is most often inherited by an autosomal dominant pathway, but rare cases of autosomal recessive transmission are known. About 500 clinical cases of the present syndrome are described, although, according to various authors, the number of clinically verified cases not confirmed by genetic verification is much higher. In addition to the given data of the clinical course of the disease, detailed results of the genetic interpretation of the hereditary syndrome are given, the modern method of pathogenetic therapy is considered – the ketogenic diet.